2022
DOI: 10.17221/187/2021-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Cow metabolic status assessed from fat/protein ratio in milk affected ovarian response and number of transferable embryos after superovulation

Abstract: This work aimed to evaluate the quantity and the quality of flushed embryos based on the metabolic status of dairy cows, lactation number, and size of the ovaries. Fifty-nine Holstein cows on 1<sup>st</sup> to 5<sup>th</sup> lactation were enrolled in the experiment. Monitoring took place during the period from October to November and from March to June. Cows with corpus luteum were included for the hormonal treatment – superovulation and timed insemination. The cow was inseminated, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Negative correlations between CYS resistance and productive traits are often mentioned in the literature (Koeck et al 2012;Gernand and Konig 2017;Jamrozik et al 2021). For example, Stadnik et al (2022) found that ovarian response depended on the metabolic status of the cow and reflected the competition for energy and nutrients between production and reproduction. Hooijer et al (2001) estimated that in the Dutch Black and White cattle population, the selection for milk yield would increase the incidence of CYS by 1.5% per 500 kg increase in milk.…”
Section: Correlations With Routinely Evaluated Traits and Indicesmentioning
confidence: 99%
“…Negative correlations between CYS resistance and productive traits are often mentioned in the literature (Koeck et al 2012;Gernand and Konig 2017;Jamrozik et al 2021). For example, Stadnik et al (2022) found that ovarian response depended on the metabolic status of the cow and reflected the competition for energy and nutrients between production and reproduction. Hooijer et al (2001) estimated that in the Dutch Black and White cattle population, the selection for milk yield would increase the incidence of CYS by 1.5% per 500 kg increase in milk.…”
Section: Correlations With Routinely Evaluated Traits and Indicesmentioning
confidence: 99%
“…Finally, the health status was studied from different points of view such as heat stress, metabolic status, semen quality etc. (Bezdicek et al 2021; Pytlik et al 2022;Stadnik et al 2022). But beyond all doubt the first task is breeding for health.…”
Section: Resultsmentioning
confidence: 99%
“…future sustainability of the milk production of the cow and the milk producing enterprise through increased costs of maintain the animal's welfare and feeding. The less frequently analysed milk components will provide important and vital information that can effectively be used in dairy management decision making to ensure the efficient production of good volumes and quality milk while ensuring high standards in the management of the dairy herd health and reproductive performance (Stadnik et al 2022). During times of climatic change, the less frequently analysed components are very important indicators in tracking the successes and failures of dairy managers to support the health and nutritional status of lactating cows and provide indicators of the welfare status and resilience of such cows (Kasna et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These more frequently analysed milk components mainly include the milk proteins, fat, and sugar, as well as the number of somatic cells (somatic cell count). Monitoring of the "less frequently analysed" milk components (urea, casein, ketones, citric acid, free fatty acids, and others) gives a strong indication of the nutritional status of dairy cows and can serve as a basis for the prevention of production disorders, and, thus, also for the promotion of animal health (Stadnik et al 2022). Literature reviews suggest a very low frequency of analysis of these components (Hanus et al 2011;Melfsen et al 2012).…”
mentioning
confidence: 99%